1990
DOI: 10.1016/s0006-3495(90)82599-6
|View full text |Cite
|
Sign up to set email alerts
|

Method of oriented circular dichroism

Abstract: We present a new method for determining the orientation of alpha-helical sections of proteins or peptides in membrane. To apply this method, membranes containing proteins must be prepared in a multilayer array. Circular dichroism (CD) spectra of the multilayer sample are then measured at the normal as well as oblique incident angles with respect to the bilayer planes; we call such spectra oriented circular dichroism (OCD). The procedure of OCD measurement, particularly the ways to avoid the spectral artifacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
312
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(326 citation statements)
references
References 19 publications
13
312
1
Order By: Relevance
“…This minority part did not contribute to the diffraction analysis but was included in the OCD measurement. In general, OCD is not sensitive to the peptide orientation within a few degrees (16). The OCD spectra shown below also indicated that the whole samples were aligned within a few degrees.…”
Section: Resultsmentioning
confidence: 71%
“…This minority part did not contribute to the diffraction analysis but was included in the OCD measurement. In general, OCD is not sensitive to the peptide orientation within a few degrees (16). The OCD spectra shown below also indicated that the whole samples were aligned within a few degrees.…”
Section: Resultsmentioning
confidence: 71%
“…However, if the helix axis has a transmembrane orientation, the incident light is parallel to the axis and several transitions are degenerate giving a characteristic CD spectrum with a positive amplitude around 200 nm and a shift of the negative amplitude to longer wavelengths (225-230 nm) (Fig. 1D) (for more information about OCD spectroscopy see (11) and references therein). CD spectroscopy on oriented supported bilayers has been successfully applied to distinguish membranesurface and transmembrane helix orientation (12).…”
Section: Resultsmentioning
confidence: 99%
“…Sigma alamethicin is a mixture of components, principally alamethicin I (85% by high-performance liquid chromatography) and alamethicin II (12%), which differ by one amino acid (36). The same material has been used in all previous studies (9,11,33,34,37,38). Two grades of melittin were used, the sequencing grade (product no.…”
Section: Methodsmentioning
confidence: 99%